ECHOES BEYOND WORDS: TOHIR MALIK’S MASTERY OF PARALINGUISTIC RESONANCE IN LITERATURE (Academicia Globe: Inderscience Research, 2023)
This article delves into the intricate world of paralinguistic tools and their profound significance in human communication, particularly within literary contexts. It underscores the critical role of nonverbal cues, specifically those associated with ocular movements and expressions, as potent conveyors of emotional depth and nuance in artistic narratives. Drawing inspiration from seminal works of the acclaimed author, Tohir Malik, the discourse sheds light on the symbiotic relationship between linguistic and paralinguistic elements, underscoring the latter’s capability to not only complement but occasionally supplant linguistic means in conveying meaning. The examination further emphasizes the imperative of recognizing these tools when mastering a language, given their intrinsic association with societal norms and inter-personal dynamics. It posits the contention that a profound understanding of a language extends beyond its structural confines, encapsulating the rich tapestry of nonverbal gestures that inherently weave into the fabric of societal interactions. This treatise, while academic in its approach, serves as a clarion call for linguists, scholars, and readers alike to accord paralinguistic means the gravity they merit in the realm of human oratory communication.